Effect of Plyometrics Training and Achievement Motivation on the Ability of Crescent Kicks in the Pencak Silat Sport - Widiastuti; Asmutiar; Ramdani Amrullah; Achmad Sofyan Hanif (JIPES - JOURNAL OF INDONESIAN PHYSICAL EDUCATION AND SPORT, 2019)
This research type was an experimental research with treatment by level design. The research is aimed at investigating the influence of plyometrics exercises and achievement motivation on the ability of crescent kick in martial arts sport. Each group performed a crescent kick test before and after treatments with the test instruments kick of martial arts sport and achievement motivation questionnaire. There were significant differences between the methods of stride jump crossover exercises:11.42, while box jump exercises: 9.59. The F-test significant showed Fcount= 88.23 higher than Ftable= 1,62, with the level of significance 0,05,There was a positive interaction between plyometricsexercise methods and achievement motivation on the ability of the crescent kick, it was indicated by the value of Fcount (Fh)= 103.04, higher than Ftable (Ft)= 1.62. The kick abilty of athletes who have high motiviation trained through stride jump crossover was better, the average value stride jump crossover=12.28,while the box jump exercises = 8.90, with the level of significance,α = 0.05 over, tcount=11.74, higher than ttable =1.68. While the kick ability of athletes who have low motivation trained through box jump was better, the average value of the atheletes’ kick ability trained through stride jump crossover = 10.13, while the box jump exercises = 10.28, with the level of significance, α = 0.05 over, tcount =0.55 lower than ttable= 1.68.